2010
DOI: 10.1152/ajpgi.00400.2009
|View full text |Cite
|
Sign up to set email alerts
|

The role of the complement and contact systems in the dextran sulfate sodium-induced colitis model: the effect of C1 inhibitor in inflammatory bowel disease

Abstract: Lu F, Fernandes SM, Davis AE 3rd. The role of the complement and contact systems in the dextran sulfate sodium-induced colitis model: the effect of C1 inhibitor in inflammatory bowel disease. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…These include cytokines, eicosanoids, reactive oxygen species, nitric oxide, and complement system activation products [4548]. Similarly, DSS-induced colitis is associated with the upregulation of different cytokines, chemokines, nitric oxide [49, 50], and inducible nitric oxide synthase (iNOS) [51].…”
Section: Pathogenesis Of Dss-induced Colitismentioning
confidence: 99%
“…These include cytokines, eicosanoids, reactive oxygen species, nitric oxide, and complement system activation products [4548]. Similarly, DSS-induced colitis is associated with the upregulation of different cytokines, chemokines, nitric oxide [49, 50], and inducible nitric oxide synthase (iNOS) [51].…”
Section: Pathogenesis Of Dss-induced Colitismentioning
confidence: 99%
“…For example, rheumatoid arthritis [134], inflammatory bowel disease [135], and the inflammatory skin conditions urticaria and psoriasis [136] can be characterized by a thrombotic phenotype. Some of this work has pointed to a role for complement activation in the pathogenesis of acute dextran sulfate sodium (DSS)-induced colitis [135], supporting the potential involvement of complement and coagulation in inflammatory bowel disease (IBD).…”
Section: Coagulation and Complementmentioning
confidence: 99%
“…For example, rheumatoid arthritis [134], inflammatory bowel disease [135], and the inflammatory skin conditions urticaria and psoriasis [136] can be characterized by a thrombotic phenotype. Some of this work has pointed to a role for complement activation in the pathogenesis of acute dextran sulfate sodium (DSS)-induced colitis [135], supporting the potential involvement of complement and coagulation in inflammatory bowel disease (IBD). In principle, complement activation in these conditions can facilitate the release of proinflammatory modulators such as C5a and TNF-α, which can in turn also induce a TF-dependent initiation of coagulation [77, 78].…”
Section: Coagulation and Complementmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicated that other factors in the complement system might also be associated with uveitis. C1 inhibitor (C1INH), a member of the serpin family, is the most important inhibitor of the complement classical pathway, which is involved in the mediation of inflammation and has been shown to be beneficial in a variety of animal models of inflammatory disease, including sepsis, inflammatory bowel disease, ischemia-reperfusion injury, endothelial cell injury, hyperacute transplant rejection and burn injury 11 12. Moreover, the gene encoding C1INH, SERPING1 , has been shown to be associated with a range of inflammatory diseases, such as age-related macular degeneration (AMD) and hereditary angioedema 13–16.…”
Section: Introductionmentioning
confidence: 99%